Contrast of warm and cold phases in the Bering Sea to understand spatial distributions of Arctic and sub-Arctic gadids - Baker, Matthew R. (Polar biology, 2021)
The influence of climate on the dynamics of Arctic gadids is of increasing interest, particularly as research and survey effort expands in the Pacific Arctic. Understanding species-specific thermal tolerance may inform models of species distribution and projections of available habitat and also clarify implications of warming for ecological communities. Analyzing shifts in species distribution in warm and cold periods, this study considers the effects of a warming climate on the distribution of two keystone Arctic gadids (polar cod, saffron cod) and two commercially important sub-Arctic gadids (walleye pollock, Pacific cod). Shifts in distribution were used to derive temperature tolerance thresholds and to project how these species might react to a warming Arctic. Significant shifts were noted in comparisons of warm (2002–2005, 2014–2016, 2017–2018) and cold (2006–2013) periods. Sub-Arctic species expanded and contracted their range as environmental conditions shifted. In contrast, Arctic species appeared constrained, such that population densities increased or decreased within the same core geographic area. Additionally, species with a demersal life history were able to tolerate a wider range of thermal conditions. These results provide important insights on relative thermal tolerance of each species, differential influence of temperature on pelagic versus demersal life histories, and depth as thermal refuge. This study demonstrates both the need to understand the spatial response of fish to changing ocean conditions in polar regions and the utility of distributional analyses to inform that effort.